Entropijska analiza sotočnih prenosnikov toplote - Galović, Antun (Strojniški vestnik, 2003)
The entropy generation in a parall-flow recuperative heat exchanger is analyzed in this paper. During the operation of a heat exchanger two sources of entropy generation normally exist: the pressure drop (friction) source and the heat-exchange source. Here, only the heat-exchanger source is considered. The analysis is performed using an analytical mathematical model and the same non-dimensional members, that were introduced into the energy analysis of heat exchangers by Bošnjaković, many years ago. The influence of the individual non-dimensional variables (the operating points of the parallel-flow heat exchanger) on the entropy generation is quantified. The results are presented non-dimensionally in diagrams, which gives them a more universal meaning. Special conditions, i.e. the boundary operating conditions,of the parallel-flow recuperator, which are identical to those for counter-flow and cross-flow exchangers, are also discussed.
Keywords: prenosniki toplote; povečevanje entropije; učinkovitost; efficiency; rešitve analitične; toplotni menjalniki; sotok; entropija